Molecular Methods in Food Safety Microbiology: Interpretation and Implications of Nucleic Acid Detection. Issue 4 (July 2014) - Ceuppens, Siele; Li, Dan; Uyttendaele, Mieke; Renault, Pierre; Ross, Paul; Ranst, Marc Van; Cocolin, Luca; Donaghy, John
Abstract Because of increasing demand for rapid results, molecular techniques are now applied for the detection of microorganisms in foodstuffs. However, interpretation problems can arise for the results generated by molecular methods in relation to the associated public health risk. Discrepancies between results obtained by molecular and conventional culture methods stem from the difference in target, namely nucleic acids instead of actively growing microorganisms. Nucleic acids constitute 5% to 15% of the dry weight of all living cells and are relatively stable, even after cell death, so they may be present in a food matrix after the foodborne microorganisms have been inactivated. Therefore, interpretation of the public health significance of positive results generated by nucleic acid detection methods warrants some additional consideration. This review discusses the stability of nucleic acids in general and highlights the persistence of microbial nucleic acids after diverse food‐processing techniques based on data from the scientific literature. Considerable amounts of DNA and RNA (intact or fragmented) persist after inactivation of bacteria and viruses by most of the commonly applied treatments in the food industry. An overview of the existing adaptations for molecular assays to cope with these problems is provided, including large fragment amplification, flotation, (enzymatic) pretreatment, and various binding assays. Finally, the negligible risks of ingesting free microbial nucleic acids are discussed and this review ends with the future perspectives of molecular methods such as next‐generation sequencing in diagnostic and source attribution food microbiology.